Military advanced regional anesthesia and analgesia handbook - Buckenmaier, Chester, III (New York, NY : Oxford University Press, 2020)
Now thoroughly revised, the primary goal of this second edition is to assist with the education of anesthesiology residents, fellows, and other allied medical professionals (special forces medics, nurse anesthetists, emergency room physicians, and others) in the art and science of acute pain medicine and regional anesthesia. It brings the expertise and lessons learned from military medicine to a larger audience in regional anesthesiology.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 15, 2020).
Keywords: Pain medicine; Medicine, Military